PENGARUH BEKERJA DARI RUMAH /WORK FROM HOME (WFH) TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PANDEGLANG TAHUN 2020 - Annisa Nurwahida; Tjahyo Rawinarno; Suhud Alynudin; Agus Widiarto (LPPM STIA Banten, 2022)
Work from home as an executor of working remotely and does not have to be in the office can affect several aspects, one of which is on employee performance. The problems in this study such as leaders who have difficulty monitoring their members/subordinates,, not all employees have electronic devices that support and the lack of direct contact interaction often occurs misscommunication.As a result, many employees enter during the work from home schedule in order to complete their work. This can affect employee performance. The purpose of this study was to determine the effect of work from home on the performance of employees at the Population and Civil Registry Office of Pandeglang Regency. The method used in this research is the Associative Quantitative method, and the data is distributed through questionnaires. And the sampling technique using saturated samples with a total of 94 samples. Based on the results of the study, it was found that there was an effect of work from home on the performance of employees at the Population and Civil Registry Office of Pandeglang Regency. The magnitude of the effect of work from hurray on the performance of employees in the Population and Civil Registry Office of Pandeglang Regency is 16.2%. While the remaining 83.8% is influenced by other variables that are not explained in this study. Suggestions from this research: it is better if the agency in the future also considers the option of organizing work from home even after the covid-19 pandemic is over.